2020
DOI: 10.1007/s12144-020-00696-2
|View full text |Cite
|
Sign up to set email alerts
|

Is a harsh childhood growth environment reflected in parental images and emotional distress in adulthood?

Abstract: Harsh parenting can predispose a child to emotional distress, whereas a supportive childhood environment furthers later subjective well-being. We investigated whether the mother’s self-reported assessment of her strictness and the adult offspring’s recollections of the disciplinary methods of their parents are reflected in the adult offspring’s recalled parental images and current emotional distress, anxiety and depression as assessed by the Hopkins Symptom Check List (HSCL-25). Further, we investigated whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…Moreover, as the perception of the usefulness of parent training is one of the important factors in the intervention (Graf et al, 2014), it seems crucial for social workers to be able to provide training that is understandable for the parents and communicate the benefits. And indeed, programs aimed at increasing the quality of children's environment, focused on fostering the skills of parents, can have long-term benefits, such as the improvement of well-being of children in adulthood (Kiviniemi et al, 2020; Vanwoerden et al, 2021). For this reason, and in line with other authors’ work, we think it would be especially the role of practitioners, their competence, experience or training, that holds an important role in successful implementation of evidence-based parenting programs (Shapiro et al, 2015; Turner et al, 2011).…”
Section: Discussion and Applications To Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, as the perception of the usefulness of parent training is one of the important factors in the intervention (Graf et al, 2014), it seems crucial for social workers to be able to provide training that is understandable for the parents and communicate the benefits. And indeed, programs aimed at increasing the quality of children's environment, focused on fostering the skills of parents, can have long-term benefits, such as the improvement of well-being of children in adulthood (Kiviniemi et al, 2020; Vanwoerden et al, 2021). For this reason, and in line with other authors’ work, we think it would be especially the role of practitioners, their competence, experience or training, that holds an important role in successful implementation of evidence-based parenting programs (Shapiro et al, 2015; Turner et al, 2011).…”
Section: Discussion and Applications To Practicementioning
confidence: 99%
“…A 2-year-long longitudinal effort from the US showed that families with high levels of conflict and low levels of positive family relations are linked to poor parental monitoring, an association of adolescents with deviant peers and further engagement in problem behavior (Ary et al, 1999). A recent Finnish longitudinal study found that parental strictness during children's upbringing can eventually lead to higher levels of emotional distress, anxiety, or depression symptoms in adulthood (Kiviniemi et al, 2020). In addition, early experiences of a negatively perceived childhood environment or lack of emotional support are connected to personality disorders such as borderline personality disorder (Vanwoerden et al, 2021).…”
mentioning
confidence: 99%